Uncommon ground - "Nilekani, Rohini" (New Delhi, 2011)
Uncommon Ground brings together titans of industry and leaders of civil society to explore eight themes that are highly relevant for our future development. Based on Rohini Nilekani$1 (Bs 2008 show on NDTV, the conversations explore the middle ground between the ideological divisions that often polarize the business and voluntary sectors. Why, despite two decades of liberalization, does economic prosperity with social inclusion remain a distant goal? Sustained GDP growth has led to the dramatic improvement in the quality of life for many. Yet millions remain untouched and are being pushed back further because of their shrinking access to the natural resources on which they now depend and because access to alternative opportunities have been denied to them. In course of these rare dialogues between leaders who have sometimes been adversaries, a number of common concerns emerge. Among others, Anand Mahindra and Medha Patkar discuss land acquisition and use; Mukesh Ambani and R.K. Pachauri debate decentralized energy options; Sunil Mittal and Aruna Roy imagine an Indian model to enhance the employability of our labor force and Yogi Deveshwar and Sunita Narain explore how industry can become more environmentally sustainable. The author, uniquely placed to moderate these discussions as she traverses both sides herself, demonstrates that the relationship between business, society and state need not be necessarily confrontational. In all areas $1 (Bfood, energy and the environment, jobs and livelihoods, transportation and mobility, poverty and financial inclusion, natural resources and economic sustainability, land use and displacement $1 (BNGOs and business can play an enabling role together with the state. Rich in insights, Uncommon Ground highlights the critical importance of dialogue in our democracy to create a shared vision of the future. It is a significant contribution to the ongoing debate on development and equitable growth in India.s
Keywords: Development issues-dialogues with business and social le